Dissociation of behavioral and endocrine stress responses by arecoline in adult zebrafish - Mondal, Koushik; Sharma, Praveen Kumar (International Journal of Aquatic Research and Environmental Studies, 2026)
Behavioral and endocrine stress responses represent two fundamental and interlinked pathways in vertebrate stress biology. Although both responses can respond to pharmacological modulation but their relationship remains poorly understood across species and comparative models. Arecoline, the key alkaloid of Areca catechu and a partial muscarinic acetylcholine receptor agonist, has been shown to induce behavioral anxiolysis in vertebrates. However, it is unclear whether this behavioral anxiolysis reduces cortisol-mediated physiological stress or, paradoxically, enhances it. This knowledge gap in comparative stress literature served as the foundation for this study by exposing adult Zebrafish (Danio rerio) to arecoline (0.5 µM, 5 µM, and 50 µM) under acute (30 minutes) and chronic (7 days) paradigms. Anxiety-like behavior in fish was assessed using vertical exploratory parameters in the novel tank test (NTT), and whole-body cortisol levels were measured using enzyme-linked immunosorbent assay (ELISA). Arecoline demonstrated duration-dependent behavioral anxiolysis by increasing top zone exploration metrices in maximum of acute and chronic parameters, yet not all reached the statistical significance but the cortisol value was significantly raised in both the exposure scenarios. Collectively, these findings indicate that arecoline alters behavioural and endocrine stress response components in adult zebrafish. The coexistence of anxiolytic-like behaviour and higher cortisol levels suggests that cholinergic modulation does not always cause behavioural and physiological stress responses to shift concurrently. These findings emphasise the need of integrating behavioural and endocrine measures in comparative stress research, as well as laying the groundwork for future study into the neuroendocrine mechanisms driving alkaloid-mediated stress regulation.